The method of heat measurement in overheated steam and its implementation in the measuring system - Lipiński, Gerard; Wawszczak, Andrzej; Karczewski, Jacek; Owsiński, Maciej; Sadura , Jolanta (Instal, 2022)
The article presents a method of measuring heat in overheated steam for the financial settlements between the heat supplier and the heat recipient. Legal regulations are presented. A description of the physical phenomena occurring during the flow of saturated and overheated steam in heating installations and the principle of heat measurement in the medium are given. The algorithm for calculating the heat meter was developed on the basis of the measurement system model. Guidelines for the design of the measurement system are given and its various configurations for various types of measurement variants and calculation of steam parameters are discussed.